Cartilage Disorders Recent Findings and Treatment - Almqvist, Karl; Ebrahim El Hamaky, Ahmed; Abdulwahab, Taiceer (IntechOpen, 2023)
Over the past few decades, there have been significant advances in our understanding of the pathophysiology of cartilage disorders, for example, the characterization of degraded cartilage using Confocal Raman Microscopy as well as the evolution of cartilage repair technologies. Cartilage disorders are complex and multifactorial, and they can cause significant pain and disability in affected joints/individuals. As such, it is essential for orthopedic surgeons to have a thorough understanding of the latest research and treatment options to provide the best possible care to their patients. This book provides a comprehensive overview of the latest research and treatment options in cartilage disorders. It presents cutting-edge research, technologies, and treatment options for orthopedic surgeons. Organized into two sections, the chapters of this book address such topics as the evaluation and management of patients with cartilage injuries, imaging and biomarker technologies, techniques to repair and regenerate damaged cartilage, and more.